Riding a Mechanical Scooter from the Inconvenient Side Promotes Muscular Balance Development in Children - Mantas Mickevicius; Danguole Satkunskiene; Saule Sipaviciene; Sigitas Kamandulis (MDPI AG, 2023)
Mechanical scooter riding is a popular physical activity among children, but little is known about the differences in muscle loading between the dominant and non-dominant sides during this activity. The objective of this study was to identify the muscle activation patterns in children's dominant and non-dominant legs as they rode scooters on the convenient and inconvenient sides. The study included nine healthy children aged 6-8. The participants rode 20 m on a mechanical scooter at a self-selected pace using both the convenient and inconvenient sides. Electromyography was used to measure the muscle activity in the dominant and non-dominant legs during the pushing and gliding phases. A 20 m sprint run was used as a control exercise to estimate the typical differences in muscle activation between the dominant and non-dominant legs. In the pushing phase, the symmetry index for five of the eight analyzed muscles exceeded 50% (p < 0.05); four of these muscles were more active in the pushing leg, and one was more active in the standing leg. In the gliding phase, four muscles were more active in the standing leg, and one was more active in the pushing leg (p < 0.05). Upon observing children who changed sides while riding a scooter, it was found that the pattern of muscle activation displayed a reverse trend that resembled the initial pattern. Our study indicated notable differences in muscle activity patterns between the dominant and non-dominant sides of individual leg muscles during children's scooter riding. These patterns were reversed when children switched sides on the scooter. These findings suggest that using both legs and switching sides while riding a scooter may be a viable strategy for promoting balanced muscular development.